An Estimation of Private Household Costs to Receive Free Oral Cholera Vaccine in Odisha, India. - Vittal Mogasale; Shantanu K Kar; Jong-Hoon Kim; Vijayalaxmi V Mogasale; Anna S Kerketta; Bikash Patnaik; Shyam Bandhu Rath; Mahesh K Puri; Young Ae You; Hemant K Khuntia; Brian Maskery; Thomas F Wierzba; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Service provider costs for vaccine delivery have been well documented; however, vaccine recipients' costs have drawn less attention. This research explores the private household out-of-pocket and opportunity costs incurred to receive free oral cholera vaccine during a mass vaccination campaign in rural Odisha, India. METHODS:Following a government-driven oral cholera mass vaccination campaign targeting population over one year of age, a questionnaire-based cross-sectional survey was conducted to estimate private household costs among vaccine recipients. The questionnaire captured travel costs as well as time and wage loss for self and accompanying persons. The productivity loss was estimated using three methods: self-reported, government defined minimum daily wages and gross domestic product per capita in Odisha. FINDINGS:On average, families were located 282.7 (SD = 254.5) meters from the nearest vaccination booths. Most family members either walked or bicycled to the vaccination sites and spent on average 26.5 minutes on travel and 15.7 minutes on waiting. Depending upon the methodology, the estimated productivity loss due to potential foregone income ranged from $0.15 to $0.29 per dose of cholera vaccine received. The private household cost of receiving oral cholera vaccine constituted 24.6% to 38.0% of overall vaccine delivery costs. INTERPRETATION:The private household costs resulting from productivity loss for receiving a free oral cholera vaccine is a substantial proportion of overall vaccine delivery cost and may influence vaccine uptake. Policy makers and program managers need to recognize the importance of private costs and consider how to balance programmatic delivery costs with private household costs to receive vaccines.